The Science of Life
XXVI, 358 p.
Keywords: The Science of Life: Contributions of Biology to Human Welfare is the first of what we anticipate will be a series of monographs resulting from activities of the Federation of American Societies for Experimental Biology. From time to time material drawn from symposia presented at the an nual meetings of the Societies, when considered suitable, will be published as separate FASEB Monographs. Usually, the material will have appeared in Federation Proceedings. Occasionally, other papers resulting from symposia, conferences, or special meetings sponsored by the Federation or one of its constituent societies will appear as a F ASEB monograph. In some instances, special articles on the same topic will be drawn together under one cover. Why should information which has already been printed and distributed as a part of the editorial content of a journal be republished as a monograph? Most of the ma terial to be included in this effort, particularly the symposia presented at the annual meetings of the six Federated Societies, will summarize the state of the art ex cellently. Such information will be of considerable value to students and teachers, especially for undergraduate honors courses or in graduate studies.